STUDY OF TROPICAL CYCLONES ACTIVITY CHANGES TEMPORALLY AND SPATIALLY IN THE INDIAN OCEAN - Sofia Lestari, Gifania
Changes analysis in tropical cyclone activity and factors identification that have the potential to cause changes over the North Indian Ocean and South Indian Ocean tropical cyclone activities are very important because tropical cyclones have a major impact. This study investigates the linear trend of tropical cyclones activity and favorable meteorological parameters for the tropical cyclone formation over a period of 50 years (1970-2019) in the North Indian Ocean and South Indian Ocean. These parameters include the sea surface temperature, 850-hPa relative vorticity, 200-hPa divergence, 500–700-hPa average relative humidity, and 200–850-hPa vertical wind shear. In both the North Indian Ocean and South Indian Ocean, Accumulated Cyclone Energy (ACE) and intensity are increasing, but the frequency of tropical cyclones has decreased. It has been shown that the spatial trend of meteorological parameters is associated quite well with the spatial trend of tropical cyclone genesis in these two regions. The trend of tropical cyclone genesis in the North Indian Ocean shows an increase over the Arabian Sea and a decrease over the Bay of Bengal, which affects the trend of tropical cyclone tracks. Meanwhile, the trend of tropical cyclone genesis in the South Indian Ocean increases near the equator and decreases at higher latitudes. This study indicates the location of increased genesis and increased intensity of tropical cyclones are leading to an increase in the number of extratropical transitions over the South Indian Ocean. In addition, the causes of decreasing frequency and increasing intensity of tropical cyclones in the North Indian Ocean and South Indian Ocean are discussed.